2018
DOI: 10.3389/fpls.2017.02258
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Bacterial Wilt in the Madagascar Highlands Caused by Andean (Phylotype IIB-1) and African (Phylotype III) Brown Rot Strains of the Ralstonia solanacearum Species Complex

Abstract: The Ralstonia solanacearum species complex (RSSC) is a highly diverse cluster of bacterial strains found worldwide, many of which are destructive and cause bacterial wilt (BW) in a wide range of host plants. In 2009, potato production in Madagascar was dramatically affected by several BW epidemics. Controlling this disease is critical for Malagasy potato producers. The first important step toward control is the characterization of strains and their putative origins. The genetic diversity and population structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 91 publications
1
25
0
Order By: Relevance
“…musacearum [16], Xanthomonas citri pv. viticola [17], and the Ralstonia solanacearum species complex [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…musacearum [16], Xanthomonas citri pv. viticola [17], and the Ralstonia solanacearum species complex [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular subtyping tools applied to bacterial pathogens include restriction-fragment length polymorphism, pulsed-field gel electrophoresis (PFGE), multiple-locus variable-number tandem-repeat analysis (VNTR/ MLVA), multilocus sequence analysis/typing (MLSA/MLST), virulence gene typing, and DNA fingerprinting patterns (12). Recent studies characterizing bacterial outbreaks in plants focused on using MLSA/MLST or MLVA (13)(14)(15)(16). However, these aforementioned tools have significant limitations because they examine only a subset of the bacterial genome of interest and thus restrict molecular epidemiological analyses (12).…”
mentioning
confidence: 99%
“…However, PCR results revealed the presence of R. solanacearum in samples from all the inoculated solanaceous plants in this study, confirming the ability of RSSC strains to survive in these plant species (Hayward, ; Elphinstone, ). More than one race or sequevar of RSSC may occur in one location at the same time (Ravelomanantsoa et al , ). A recent study in Rwanda (Mutimawurugo et al , ) reported the presence of biovar 3 from potato fields in Kinigi.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there are no known cultivars with resistance to the RSSC. A pathogen race at one location may overcome the resistance effective at another location, and more than one race may occur in a given field or location (Ravelomanantsoa et al, 2018). In addition, potato cultivars show variable reactions in different environments and in different seasons within the same environment (French et al, 1998;Ateka et al, 2001).…”
mentioning
confidence: 99%